Kisah Kelabu di Balik Maraknya Pers Lokal Di Kalimantan - Muhamad Sulhan (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2006)
Drwan upon three filters of political econmic analysis of mass media, namely concentrated ownership, advertising and the dynamism of audience, this article uncover a local press in Kalimantan.For the sake gaining maximal profit they fail to perform as watch dog and safeguarding moral idealism